Mapping of Learning Guidance Competencies in Dealing with Digital Learning - Irwan, Mahfuzi; Lubis, Putri Ramadhani; Nasution, Ikhwanu Sopia; Wulansari, Desi; Siahaan, Sisilia Brigita; Pasaribu, Dhieta Naiya Arthameyvia (Raudhah Publisher, 2024)
Industrial Revolution 4.0 is a major phenomenon that has changed the global landscape in various aspects of life, including education. These changes have a significant impact on the competencies of learning teachers, who must adapt quickly to meet the demands of this digital era. In the Industrial Revolution 4.0, the role of tutors has changed to become more than just a teacher. They must be the main drivers of project-based and collaborative learning, where learning citizens can work in teams to develop projects that are relevant to the real world. Learning tutors must encourage creativity, courage to think, and the ability to solve students' problems. This change requires learning teachers to explore the spirit of exploration and innovation within themselves, so that they can inspire students to do the same. To face revolution 4.0, the author intends to design the competencies that learning teachers must have, for example the professionalism competencies of learning teachers. The research method that researchers use is a qualitative approach and the research data collection that will be used is a questionnaire. It is hoped that the professional competencies possessed by the learning tutors can improve the teaching abilities of the learning tutors and with the professional competencies they have, it is hoped that the learning tutors can face the industrial revolution 4.0.